Victimological Review of Psychological Fulfillment Towards Correctional Students at The Class I of Juvenile Rehabilitation Institute in Tangerang City - Inggrit Steffi Lantang; Rena Yulia; Aliyth Prakarsa (Epistemik Press, 2021)
Adjudicated juvenile described as a child which has to undergo a sentence determined by court’s judge in Correctional Institution of Educated Child and is referred to as a Educated Child. The Juvenile Justice System as an effort to educated child without ignoring their basic needs which is mainly to their psychological consequences facing adjudication at the court, but is questioned, until now there has been no clarity on fullfiling their psychological rights. Based on these problems, the researcher focused on victimological perspective how correctional students became victims of the Correctional Institution of Educated Child and how the psychological rights are carried in Correctional Institution of Educated Child Class I Tangerang City. The research uses legal empiric or sociological method, data and analytical descriptive approach. The research source mainly from secondary data and also supported by interviews with several parties in the Correctional Institution of Educated Child Class I Tangerang City and then analyzed qualitatively. The results of the research are adjudicated juveniles are sometimes individual and direct victims, they suffered losses because their rights were not properly fullfilled, their lossesare in the form of mental injuries due to lack of social support, authority and responsibilities regulated by the Juvenile Justice System has not been implemented optimally due to the abuse of power of officers of Correctional Institution of Educated Child, that do not provide guidance programs to fulfill the psychological rights of Educated Child to date and in the implementation of psychological rights fulfillment for Educated Child in the Correctional Institution of Educated Child Class I Tangerang City have not been implemented properly because there is no technical implementation of specific regulations related to special programs for psychological development and the absence of professional officers for fulfillment psychological of Educated Child.